Proceedings Frontiers in Education 35th Annual Conference
DOI: 10.1109/fie.2005.1612279
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Remote Networking Laboratories

Abstract: -The Interdisciplinary TelecommunicationsProgram at the University of Colorado has developed an internet based remote laboratory environment for master's level graduate students; our suite of telecommunications experiments substantially extends prior work focused on networking equipment, by (1) providing a systems focus, (2) enabling multiple reinforcing methods of accessing the educational material, (3) providing a configuration matrix to support realtime network reconfigurations (of real network elements) (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…It has been the understanding of several authors [7], [8], [13] the need for the development of well-designed didactical tasks in order to accompany students in their exploration of these tools and proper feedback in order for them to evolve. With the lack of contact time, students might be overwhelmed if teachers give them too many resources to freely explore.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been the understanding of several authors [7], [8], [13] the need for the development of well-designed didactical tasks in order to accompany students in their exploration of these tools and proper feedback in order for them to evolve. With the lack of contact time, students might be overwhelmed if teachers give them too many resources to freely explore.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is still some controversy in its efficacy in general [5], [6], [7], [8] teachers are tending to use it more often, either instead or as a complement to the traditional hands-on lab. Three factors also contributed to the growth of this usage: i) the growth of the number of students, specially a few decades ago; ii) the Bologna reform and the reduced amount of contact time between teachers and students [3]; and, iii) the more limited budget Universities have, which leads to too large classes and to very limited time for each student to really operate in laboratory with the equipment (too large groups implies that not everyone gets the chance to perform real work) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote laboratories provide students with a real environment to carry out practical activities. They are different from simulators because the latter are not real environments, as shown in [10] and [13]. In a VLE, a remote laboratory is a key resource since it is the only solution that allows students to work with real devices since it cannot be assumed that students will have such devices at home.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate comparative literature review and assessment of the effectiveness of VNLabs is found in [9] and [10].…”
Section: Introductionmentioning
confidence: 99%